1984
DOI: 10.2169/internalmedicine1962.23.135
|View full text |Cite
|
Sign up to set email alerts
|

Amegakaryocytic thrombocytopenia associated with systemic lupus erythematosus successfully treated by a high-dose prednisolone therapy.

Abstract: A patient with systemic lupus erythematosus (SLE) developed amegakaryocytic thrombocytopenic purpura. The absence of a drug relationship or other identifiable underlying cause madeus consider this to be a rare manifestation of SLE. Her thrombocytopenia, which initially appeared to be steroid-resistant, ultimately improved following a prolonged high-dose prednisolone therapy. To our knowledge, this is the second case of amegakaryocytic thrombocytopenia associated with SLEin the literature. The possibility that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although the first case of MAS secondary to SLE was reported in 1984, it was not until a 1991 report of 6 cases that MAS was recognized as a complication of SLE . A 2014 systematic review found 133 cases of MAS secondary to adult SLE reported in the literature, making it the most common cause of MAS in adults with rheumatic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Although the first case of MAS secondary to SLE was reported in 1984, it was not until a 1991 report of 6 cases that MAS was recognized as a complication of SLE . A 2014 systematic review found 133 cases of MAS secondary to adult SLE reported in the literature, making it the most common cause of MAS in adults with rheumatic diseases .…”
Section: Discussionmentioning
confidence: 99%
“…As therapeutic strategies for AATP, glucocorticoid, 1 , 3 , 4 , 7 , 8 , 10 - 12 , 22 , 23 , 25 , 26 high-dose IVIg, 1 , 7 , 8 , 22 , 23 anti-thymocyte globulin, 4 , 9 cyclosporine A, 7 , 9 - 12 , 23 rituximab, 10 , 11 splenectomy, 8 allogeneic hematopoietic stem cell transplantation, 8 and agonists for c-Mpl, 10 androgens, 5 and vincristine 7 , 8 have been employed. Of these, glucocorticoid therapy, which is widely used and effective for ITP, is less effective for AATP.…”
Section: Discussionmentioning
confidence: 99%
“…Amegakaryocytic thrombocytopenia may be a primary disorder itself 10 or may be seen in aplastic anemia, 11 preleukemia, 11 and in systemic lupus erythematosus. 12 - 14 It has also been reported in patients with Graves’ disease treated with radioiodine in the past, 15 in congenital rubella, dengue fever, nutritional B 12 deficiency, ethanol abuse, and certain congenital disorders like the thrombocytopenia-absent radius (TAR) syndrome.…”
Section: Discussionmentioning
confidence: 98%